Dual mechanisms of G3 against Vibrio parahaemolyticus in shrimp aquaculture - Cuixia Chen; Yangyang Ge; Qilong Gu; Tianling Wang; Yanyan Yang; Jinpeng Hu; Kang Gao; Xing Zhou; Hui Li (Aquaculture Reports)
Bacterial diseases mainly caused by Vibrio species pose a serious threat to shrimp aquaculture and lead to the sudden mass mortalities and huge economics losses. The unfavorable side effects and emergence of superbugs in traditional antibiotic treatment makes development of excellent antibacterial agents especially urgent. Antimicrobial peptides (AMPs), which usually have high antibacterial activity and low potential to induce bacterial resistance, are considered as the promising alternatives to conventional antibiotics. However, their anti-Vibrio mechanisms have not yet reached a consensus. In this study, a pathogenic Vibrio strain was isolated from the cultured shrimp and was identified as Vibrio parahaemolyticus UPC-1 (V. Parahaemolyticus UPC-1). Studies showed that G3 efficiently protected shrimp from V. Parahaemolyticus UPC-1 infection through two independent ways. In one way, G3 balanced the bacterial community of shrimp gut by selectively killing the pathogenic Vibrio bacteria. In the other way, G3 markedly reduced the robust inflammation effects induced by Vibrio infection. Such efficient anti-Vibrio activity of G3 endows it great potential in the treatment of Vibrio infections in shrimp aquaculture.